Pengaruh Pestisida dari Aktivitas Pertanian Terhadap Konsentrasi Merkuri (Hg) pada Sungai Sumur Beremas Kota Sungai Penuh - Anggrika Riyanti; Marhadi Marhadi; Syskha Eka Patri (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Agricultural activities cannot be separated from the use of pesticides to control plant-disturbing organisms. The mercury (Hg) content in pesticides cannot be naturally degraded on agricultural land, so it will be carried off by run-off into the waters. Pesticide’s run-off from agricultural activity along the Sumur Beremas River has an effect in increasing mercury concentrations in the river. This study aims to analyze the effect of pesticide use on mercury concentrations in the Sumur Beremas River and to analyze the capacity of river pollution loads. The effect of pesticide on mercury concentrations was analyzed using Pearson correlation. The capacity of Sumur Beremas River's pollution loads against mercury was analyzed using mass balance method. The results showed that the use of pesticides had a significant effect on the increase in mercury concentrations in river water. The greatest correlation value occurs in downstream of irrigation, namely 0.977, which indicates the high run-off that occurs from agricultural area to the irrigation flow. The concentration of mercury based on the analysis of river pollution loads is 0.00242 ppm, exceeding the standard PP no. 82 of 2001 Class II, 0.002 ppm, which indicates that Sumur Beremas River is no longer able to accommodate the load of mercury pollution.